Efektivitas Perubahan Lembaga Pendidikan Tenaga Kependidikan (LPTK)/Institut Keguruan dan Ilmu Pendidikan (IKIP) menjadi Universitas - Idris H.M Noor (Jurnal Pendidikan dan Kebudayaan, 2013)
The research investigates the effectiveness of the status change of teacher training institute into university. Research uses mixed quantitative and qualitative approach, evaluation and case study methods. sampling are stratified and purposive from eight public universities. Data collecting was Focus Group Discussion (FGD), kuessioner, and interview. Data analysis used percentage quantitative and case analysis of the unique of each study program at each university. The study shows: 1) universities are still keeping their roles as their core business to produce teachers and educational administrators, 2) Students competence significantly improves due to the education and non education program of the study reciprocally give or help each other as well as share their experience to enhance students’ competence in science and social subjects, 3) the enrolement of students tends to be increased every year with high academic qualification candidates, 4) curriculum consists of education and non education (pure science and social subjects), 5) lectrurers’ qualification also increases significantly, srata 1 tends to be decrease, while master dan doctor degree-S2/S3 increase significantly every year/period, 6) budget of each university and faculty is different due to the different location of universities and needs of each faculty, and 7) students cummulative achievement index (3.275) increases every year.